2022
DOI: 10.3389/fchem.2022.1069450
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer effect of zinc oxide nanoparticles prepared by varying entry time of ion carriers against A431 skin cancer cells in vitro

Abstract: Although, zinc oxide nanoparticles (ZRTs) as an anti-cancer agent have been the subject of numerous studies, none of the reports has investigated the impact of the reaction entry time of ion-carriers on the preparation of ZRTs. Therefore, we synthesized variants of ZRTs by extending the entry time of NaOH (that acts as a carrier of hydroxyl ions) in the reaction mixture. The anti-proliferative action, morphological changes, reactive oxygen species (ROS) production, and nuclear apoptosis of ZRTs on human A431 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 98 publications
(123 reference statements)
0
13
0
Order By: Relevance
“…The effects of ZRT‐1 and ZRT‐2 on human A431 skin cancer cells were then evaluated, including antiproliferative effects, morphological changes, ROS production, and nuclear apoptosis. The results demonstrate that different forms of ZRTs exhibit varying anticancer effects 46 . Furthermore, combining ZnO NPs with a dextran grafted polyacrylamide carrier can enhance apoptosis induction in vitro in prostate cancer cells.…”
Section: Nano Platform Of Zno Nmts For Cancer Treatmentmentioning
confidence: 83%
See 2 more Smart Citations
“…The effects of ZRT‐1 and ZRT‐2 on human A431 skin cancer cells were then evaluated, including antiproliferative effects, morphological changes, ROS production, and nuclear apoptosis. The results demonstrate that different forms of ZRTs exhibit varying anticancer effects 46 . Furthermore, combining ZnO NPs with a dextran grafted polyacrylamide carrier can enhance apoptosis induction in vitro in prostate cancer cells.…”
Section: Nano Platform Of Zno Nmts For Cancer Treatmentmentioning
confidence: 83%
“…Another study revealed that ZnO NPs (ZRts) exert antiproliferative effects, induce morphological changes, ROS production, and nuclear apoptosis in the human skin cancer cell line A431. Among the ZRts, ZRt‐2 demonstrated superior anticancer potential on A431 cells 46 . Furthermore, ZnO NPs selectively induced apoptosis in diffuse large B‐cell lymphoma cells (DLBCL) and modulated their transcriptome.…”
Section: Effect Of Zno Nps On Tumor Cell Model In Vitromentioning
confidence: 99%
See 1 more Smart Citation
“…Apoptosis, also known as programmed cell death, is a major physiological process that maintains tissue homeostasis by removing damaged and/or premalignant cells [71]. Apoptosis is a pivotal factor that plays a major role in suppressing tumor growth [39].…”
Section: Discussionmentioning
confidence: 99%
“…[9] These nanoparticles exhibit unique physicochemical properties, including size-dependent reactivity and enhanced surface area, which make them attractive candidates for therapeutic applications. [10] These nanoparticles exhibit excellent antimicrobial, [11] anticancer, [12,13] and antidiabetic [14] properties, making them promising candidates for therapeutic interventions. To harness the potential of AgNPs for addressing cancer and diabetes, researchers have explored various methods of nanoparticles synthesis [15] including physical, chemical, and biological methods.…”
Section: Introductionmentioning
confidence: 99%